Sejarah Peradilan Agama di Indonesia - Andi Akram (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2008)
The up and down of Islamic court in Indonesia is related to the dynamic of social and politic. In colonialism era, this court is concerned only in marriage, divorce, and marriage reconciliation . Nowadays, according to UU no. 4 th. 2004, its function is divided into three parts executive, legislative, and judicial.